The Impact of Accounting Thought Direction of Fair value on the Relevance: An Applied Study of a Sample of the Listed Banks Listed in the Iraqi Stock Exchange (Journal of Accounting and Financial Studies ( JAFS ), 2019)
In accounting studies, more than one method is used to measure income and balance sheets elements. One of these methods is called the fair value, which use to determine the assets and liabilities ad it includes the benefits or self-satisfaction ability. This paper aims to focus on the importance of fair value as a basis of accounting measurement and its effects to achieve the relevant characteristics by using the equation is used by (Kythreotis) in his research, And Also , Editing this equation depending on the financial data and information of Iraqi Banks as a case.